2020
DOI: 10.3390/mi12010012
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis-Based Positioning of Carbon Nanotubes for Wafer-Scale Fabrication of Carbon Nanotube Devices

Abstract: In this paper, we report the wafer-scale fabrication of carbon nanotube field-effect transistors (CNTFETs) with the dielectrophoresis (DEP) method. Semiconducting carbon nanotubes (CNTs) were positioned as the active channel material in the fabrication of carbon nanotube field-effect transistors (CNTFETs) with dielectrophoresis (DEP). The drain-source current (IDS) was measured as a function of the drain-source voltage (VDS) and gate-source voltage (VGS) from each CNTFET on the fabricated wafer. The IDS on/off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In the rotational motion, the angular velocity of a CNT in an electrical field is described by equation (20) [93]…”
Section: Carbon Nanotube Velocity In Mediumsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rotational motion, the angular velocity of a CNT in an electrical field is described by equation (20) [93]…”
Section: Carbon Nanotube Velocity In Mediumsmentioning
confidence: 99%
“…Although a high yield was obtained, the variation in the resistance in 7465 CNTFET devices was between 100 k Ohm and 10 M Ohm. Kimbrough et al employed the DEP force in the fabrication of wafer-scale CNTFETs, as shown in figure 15(f) [20]. The yield of the functional devices was 87%, with 30% having I DS on/off current ratio larger than 20, while the remaining devices had I DS on/off current ratio less than 20.…”
Section: Cnt-based Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Carbon Nanotubes (CNTs) have come to the fore as most promising materials and are being considered for a wide variety of applications ranging from large-scale structure to nanometer-scale electronics because of their superior mechanical and physical properties [32,33]. CNTs were discovered accidentally by Japanese physicist S. lijima [34] in 1991 when performing experiments on carbonium.…”
Section: A Brief On Carbon Nanotube Field Effect Transistors (Cntfets)mentioning
confidence: 99%
“…density and the degree of order), which in turn will greatly affect the conductivity of the transistor. Limited by the poor purification technology of sc-SWCNT, early dielectrophoresis reports on low purity sc-SWCNTs dispersion generally had very low on/off current ratios and poor device performace of FETs [23,24], just because m-SWCNTs would suffer a larger dielectrophoretic force (F DEP ) than sc-SWCNTs under an ununiform electric field, leading a preferential collection and arrangement of the m-SWCNTs in the channel to the sc-SWCNTs. As a result, dielectrophoresis method was ever used to effectively separate m-SWCNTs from a mixed SWCNTs [25].…”
Section: Introductionmentioning
confidence: 99%